Laser-induced reduced-graphene-oxide micro-optics patterned by femtosecond laser direct writing - Low, Mun Ji (2020)
Direct laser writing has emerged as a promising technology for facile and cost-effective single-step manufacturing of laser-induced reduced-graphene-oxide (LIRGO). Since LIRGO’s optical properties can be controlled during photoreduction process, laser-patterned micro-optics can work as light-weight diffractive optical elements over conventional bulk refractive optics. Here, we present ultra-thin diffractive LIRGO micro-optics patterned by femtosecond laser direct writing (FsLDW) with high spatial resolution and wide design flexibility based on the wide parametric tunability of femtosecond pulsed lasers over conventional continuous-wave or long-pulsed lasers. By extensive parametric control of average power (10–120 mW), pulse repetition rate (1–500 kHz) and scan speed (1–100 mm/s) in FsLDW, ultra-thin micro-optics were patterned at three patterning regimes: non-thermal photoreduction regime, thermal photoreduction regime, and ablation regime. The optical performances of Fresnel zone plates (FZP) fabricated under the three regimes were evaluated and compared; the results were 0.7%, 2.4%, and 3.8% for focusing efficiency, 12.2 µm, 13.2 µm, and 12 µm for focal spot size, 1.39 mm, 1.89 mm, and 1.77 mm for depth-of-focus for FZPs designed to 15 mm focal length with 10 concentric rings. This fabrication technique provides wide design flexibility to various planar LIRGO micro-optics for microfluidics, lab-on-a-chip, skin-attachable biomedical imaging, and micro photonic devices.